K(Ca)3.1 channel-blockade attenuates airway pathophysiology in a sheep model of chronic asthma. - Joanne Van Der Velden; Grace Sum; Donna Barker; Emmanuel Koumoundouros; Garry Barcham; Heike Wulff; Neil Castle; Peter Bradding; Kenneth Snibson (PLoS ONE)
Background The Ca(2+)-activated K(+) channel K(Ca)3.1 is expressed in several structural and inflammatory airway cell types and is proposed to play an important role in the pathophysiology of asthma. The aim of the current study was to determine whether inhibition of K(Ca)3.1 modifies experimental asthma in sheep. Methodology and principal findings Atopic sheep were administered either 30 mg/kg Senicapoc (ICA-17073), a selective inhibitor of the K(Ca)3.1-channel, or vehicle alone (0.5% methylcellulose) twice daily (orally). Both groups received fortnightly aerosol challenges with house dust mite allergen for fourteen weeks. A separate sheep group received no allergen challenges or drug treatment. In the vehicle-control group, twelve weeks of allergen challenges resulted in a 60±19% increase in resting airway resistance, and this was completely attenuated by treatment with Senicapoc (0.25±12%; n = 10, P = 0.0147). The vehicle-control group had a peak-early phase increase in lung resistance of 82±21%, and this was reduced by 58% with Senicapoc treatment (24±14%; n = 10, P = 0.0288). Senicapoc-treated sheep also demonstrated reduced airway hyperresponsiveness, requiring a significantly higher dose of carbachol to increase resistance by 100% compared to allergen-challenged vehicle-control sheep (20±5 vs. 52±18 breath-units of carbachol; n = 10, P = 0.0340). Senicapoc also significantly reduced eosinophil numbers in bronchoalveolar lavage taken 48 hours post-allergen challenge, and reduced vascular remodelling. Conclusions These findings suggest that K(Ca)3.1-activity contributes to allergen-induced airway responses, inflammation and vascular remodelling in a sheep model of asthma, and that inhibition of K(Ca)3.1 may be an effective strategy for blocking allergen-induced airway inflammation and hyperresponsiveness in humans.